استخدام النفايات البلاستيكية في العزل الحراري - حمود, أريج (Latakia University Journal -Engineering Sciences Series, 2018)
يهدف البحث إلى استخدام النفايات البلاستيكيه مع بعض المواد البلاستيكية الجديدة المتوفرة في السوق للحصول على مواد تستخدم في العزل الحراري وتؤمن في نفس الوقت التخلص من النفايات البلاستيكية. لتحقيق هذا الهدف تم تشكيل مجموعتين من العينات, المجموعة الأولى ناتجة عن مزج مادة البولي استر غير المشبع UPR مع نفايات بلاستيكية ممثلة بالبولي ستيارين القابل للتمدد EPS تم إضافتها بنسب مختلفة. المجموعة الثانية ناتجة عن تشكيل مجروش البولي إيثلين المعاد تدويره RLDPEالمحضر من رقائق البيوت البلاستيكية التالفة مع نفايات خشبية ناتجه عن ورشات النجارة.تم قياس معامل التوصيل الحراري وقياس الكثافة لجميع العينات. وأشارت النتائج الى أنه يحدث انخفاض واضح بمعامل التوصيل نتيجة اضافة كل من EPS والستيارين لمادة UPR، وتبين إمكانية استخدام النفايات العضوية بأي شكل من الأشكال مع نفاياتRLDPE وحدثت زيادة بمعامل التوصيل الحراري إذا كان شكل المالئ العضوي بودرة أو جزيئات عشوائية وانخفاض طفيف في معامل الإيصالية إذا كانت جزيئات المالئ العضوي متوسطة الحجم.The present research, aims to use the wasted plastic with some new plastic materials available from the market for producing a thermal insulator, and reducing the plastic waste. This was done by forming two samples:the first sample: was done by mixing the unsaturated polyester resin UPR with waste old expandable polystyrene EPS, in different percentages.The second sample: produced from the crushed recycled low density polyethylene obtained from old greenhouses.This way of mixing, will help us to study the thermal conductivity coefficient measurement and the measured density of all the produced samples. Our results showed that dissolving UPR to EPS materials will reduce clearly the conductivity coefficient and reduce the panels cost-production,after adding the EPS and styrene substance to UPR. This also show the possibility of using organic-waste in any way with crushed waste without any later processions.this also will affect the thermal conductivity factor according to the organic particles size mixe.